(untitled) (Journal of the College of Basic Education, 2022)
Creativity in Iraq in the field of the novel has been characterized by vigorous activity in recent years by novelists, some of whom write in the creative field back to the seventies and even the sixties of the last century, and this creative movement coincided with a critical movement that began to be carried out by critics in newspapers and magazines, especially from specialized university In order to establish traditions of criticism related to narrative literature in Iraq. And while this effort went to the work of the criticism machine in some texts on the one hand, and the documentation of the creative movement in Iraq in order to establish a coherent and homogeneous creative and intellectual cultural system on the other hand, the novel still needs more research in its forms and contents as a creative feature of this age .